Three-Dimensional Numerical Study of Flow Particle Paths in Rotating Detonation Engine with a Hollow Combustor. Issue 6 (3rd June 2017) - Yao, Songbai; Tang, Xinmeng; Wang, Jianping; Shao, Yetao; Zhou, Rui
ABSTRACT: A three-dimensional simulation is performed to study rotating detonation engines (RDEs) with a hollow combustor. The simulation tracks some representative flow particles and makes an analysis of their evolution process in the rotating detonation flow, including their trajectories and the variation of their physical properties. The study shows that there are mainly two types of trajectories of these tracked particles. The particles in the outer region of the chamber present smooth paths and flow downstream quickly along the outer wall. The particles in the inner region, by contrast, show relatively winding paths before passing through the chamber. Overall, most of the flow particles are ejected almost along the axial direction. The physical properties of the flow particles change rapidly and evidently when they encounter the detonation front. The oblique shock wave induced by the detonation wave has a compression effect on the flow particles. This compression effect, however, is much smaller compared with that of the detonation front. The present study helps to explore some details of the detonation flow in the hollow combustor and shows that the hollow RDE has the advantage of generating a stable thrust.